MANAJEMEN ADAPTASI PEMBELAJARAN KURIKULUM 2013 KE KURIKULUM 2006 (KTSP) PADA SISWA KELAS I SDN SONDAKAN SURAKARTA - Wahdan Najib Habiby (Profesi Pendidikan Dasar, 2017)
Education is one of the most important things in determining the progress of a nation. Indonesian government always strives to develop education, such as the curriculum which always developed and change. Recently in Indonesia has experienced a shift from a curriculum of 2006 (KTSP) to Curriculum 2013. Both of the curriculum has a lot of significant differences. Unfortunately when the materials of the new curriculum for elemantary school uncomplate, the goverment took decision to implementation in the school. So there is two kind of curriculum implementing in one school, and its terrible. The problem in implementing of this new curriculum saw in the SDN Sondakan 11 Surakarta where grade 1 and 4 using curriculum 2013 and other grade using curriculum 2006. When the student grade 1 moving to second grade they got problem and need adaptation in teaching learning proces. With the management / management of curriculum adaptation is expected that students can follow the learning activities with two different curriculum well.